A taxonomic revision of the seed-harvester ant genus Pogonomyrmex (Hymenoptera: Formicidae) on Hispaniola - Johnson, Robert A.; Cover, Stefan P. (Zootaxa, 2015)
We revise species of seed-harvester ants in the genus Pogonomyrmex (subfamily Myrmicinae) that occur on the Caribbean island of Hispaniola. Three species are recognized: P. aterrimus Wheeler (new status), P. saucius Wheeler and Mann, and P. schmitti Forel. Pogonomyrmex schmitti sublaevigatus Wheeler (= schmitti) and P. schmitti darlingtoni Wheeler (= aterrimus) are synonomized. We also describe the queen of P. aterrimus and P. saucius, and provide information on biology, distribution maps, and a key to workers and queens.